COVID-19: a multi-organ perspective - Guarienti, Fabiana Amaral; Gonçalves, João Ismael Budelon; Gonçalves, Júlia Budelon; Antônio Costa Xavier, Fernando; Marinowic, Daniel; Machado, Denise Cantarelli (Frontiers in Cellular and Infection Microbiology, 2024)
In this mini review, we explore the complex network of inflammatory reactions incited by SARS-CoV-2 infection, which extends its reach well beyond the respiratory domain to influence various organ systems. Synthesizing existing literature, it elucidates how the hyperinflammation observed in COVID-19 patients affects multiple organ systems leading to physiological impairments that can persist over long after the resolution of infection. By exploring the systemic manifestations of this inflammatory cascade, from acute respiratory distress syndrome (ARDS) to renal impairment and neurological sequelae, the review highlights the profound interplay between inflammation and organ dysfunction. By synthesizing recent research and clinical observations, this mini review aims to provide an overview of the systemic interactions and complications associated with COVID-19, underscoring the need for an integrated approach to treatment and management. Understanding these systemic effects is crucial for improving patient outcomes and preparing for future public health challenges.